Study on the Current Status of Egg Freezing Technology and Policies for Single Women - Mengyao YAN; Yuanli LIU (Yixue yu zhexue, 2025)
By comparing the regulations and practices of egg freezing in some countries and regions, this paper summarizes the current situation of egg freezing for single women and discusses successful experiences of international egg freezing services. International practices demonstrate that the safety and ethical aspects of egg freezing policy are well within control. Based on this, this paper calls for a timely adjustment of existing policies in China to optimize regulations on egg freezing for single women, providing a legal, safe and accessible service pathway to help women who delay childbirth for various reasons preserve their reproductive capacity and meet their needs for fertility protection. By drawing on international practical experience, we should explore the establishment of a scientific and rational service system tailored to China's national conditions, so as to better respond to social needs, adapt to technological advances, and positively address the challenges posed by changes in population structure.